2015
DOI: 10.1227/neu.0000000000000698
|View full text |Cite
|
Sign up to set email alerts
|

Initial Multicenter Technical Experience With the Apollo Device for Minimally Invasive Intracerebral Hematoma Evacuation

Abstract: Minimally invasive evacuation of ICH and intraventricular hemorrhage can be achieved with the Apollo system. Future work will be required to determine which subset of patients are most likely to benefit from this promising technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 25 publications
4
42
0
Order By: Relevance
“…Since approval, the system has been used clinically for the evacuation of both ventricular and cerebral hemorrhages (off-label). 23,24 In March of 2016, the clearence for the Apollo System was expanded with the current labeling: device is a nonclogging aspiration-irrigation system which allows the removal of hemorrhagic products through a low-profile (2.1 or 2.6 mm diameter) wand for the controlled aspiration of soft tissue and fluid during surgery of the ventricular system or cerebrum. A vibrational element housed within the wand vibrates at high frequency to break down the hemorrhagic products inside of the wand and prevent clogging.…”
Section: New Mis Technologies For Ich Evacuationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since approval, the system has been used clinically for the evacuation of both ventricular and cerebral hemorrhages (off-label). 23,24 In March of 2016, the clearence for the Apollo System was expanded with the current labeling: device is a nonclogging aspiration-irrigation system which allows the removal of hemorrhagic products through a low-profile (2.1 or 2.6 mm diameter) wand for the controlled aspiration of soft tissue and fluid during surgery of the ventricular system or cerebrum. A vibrational element housed within the wand vibrates at high frequency to break down the hemorrhagic products inside of the wand and prevent clogging.…”
Section: New Mis Technologies For Ich Evacuationmentioning
confidence: 99%
“…25 The feasibility of the Apollo System for the removal of ICH has similarly been demonstrated in initial case reports. 23,24 Spiotta et al reported a retrospective analysis of 29 patients with ICH treated with the Apollo system at 4 centers. The authors reported a mean reduction in hemorrhage volume of 54%, with 2 procedural complications.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…The MISTIE phase II trial showed a trend towards improved outcomes in the surgical patients compared to those in the medically managed patients. In addition, the ongoing MISTIE III trial added a stereotactic CT-guided endoscopic surgery arm [18][19][20][21]. In the present study, we attempted to compare the short-term and long-term effectiveness of sICH treatment, including medical treatment (control) and surgical intervention (craniotomy and endoscope).…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to the ICES technique, in most cases, no drainage catheters were placed following the initial evacuation 48 .…”
Section: The Apollo Systemmentioning
confidence: 99%